1992
DOI: 10.1530/jrf.0.0940085
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of plasma melatonin and luteinizing hormone in domestic gilts reared under artificial long or short days

Abstract: Plasma melatonin concentrations were measured every 1-2 h over 24 h and plasma luteinizing hormone (LH) concentrations every 15 min over 12 h in domestic gilts reared under artificial light regimens that had previously been used to demonstrate photoperiodic effects on puberty. In Expt 1, the light regimens both commenced at 12 h light: 12 h dark (12L:12D) and either increased (long-day) or decreased (short-day) by 15 min/week until the long-day gilts were receiving 16L:8D and the short-day gilts 8L:16D at samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…Recently, we have shown that domestic gilts display a diurnal variation in plasma melatonin concentration (Paterson et al, 1992) which is similar to that observed in other species that use melatonin for this purpose (Lincoln et al, 1982;Arendt, 1986). The pattern of plasma melatonin we observed in the dark phase, with peak concentrations measured 1-2 h after lights off followed by a gradual decline towards baseline, was almost identical to that reported for European wild pigs (Mauget et al, 1990).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recently, we have shown that domestic gilts display a diurnal variation in plasma melatonin concentration (Paterson et al, 1992) which is similar to that observed in other species that use melatonin for this purpose (Lincoln et al, 1982;Arendt, 1986). The pattern of plasma melatonin we observed in the dark phase, with peak concentrations measured 1-2 h after lights off followed by a gradual decline towards baseline, was almost identical to that reported for European wild pigs (Mauget et al, 1990).…”
Section: Introductionsupporting
confidence: 83%
“…Reproductive activity in this species exhibits a high degree of seasonality, which is controlled by photoperiod (Mauget, 1982) and, as in other species, the diurnal variation in melatonin is believed to be the means by which photoperiodic information is transduced. The findings of Paterson et al (1992) suggest that this physiological mechanism also operates in domestic pigs.…”
Section: Introductionmentioning
confidence: 73%
“…The inverse relationship between photoperiod and the length of the nocturnal peak concentration of melatonin in the pineal and in serum has been demonstrated in a number of species [8,[22][23][24][25]. In sheep, it has also been shown that systemic infusions that restore a rhythm of melatonin in the blood of pinealectomized animals can also induce neuroendocrine responses characteristic of long or short photoperiods [8].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin concentration in the medium samples was measured by a direct RIA with the use of Prospect 6C antiserum (Paterson et al 1992) and 3 H-melatonin according to the previously described and validated procedure (Fraser et al 1983, Prusik 2005.…”
Section: Melatonin Radioimmunoassaymentioning
confidence: 99%